PERBEDAAN TINGKAT KEFASIHAN BACAAN AL-QUR’AN SANTRI SEBELUM DAN SESUDAH PEMBELAJARAN METODE QIRO’ATI DI PONDOK PESANTREN ROUDLOTUL QUR’AN DARUL FALAH III CUKIR - Arvine Fiona; Sholihul Anshori (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This study aims to determine the difference in the level of fluency in reading the Al Qur'an of students before and after learning the qiro'ati method at the Roudlotul Qur'an Darul Falah III Cukir Islamic boarding school. This research uses quantitative descriptive research with a pre-experimental research type and the research design used is one-group pretest-posttest. The population of this study was 150 people with a sample size of 30 people. The sampling technique for this research was determined using the Stratified Random Sampling technique. Sampling is used in a population that has a stratified structure that will be used as respondents by taking a group that is considered to represent the entire population. Documentation and tests are used as research instruments to obtain data in the form of descriptive statistics and inferential statistics. The results obtained from this research are 1) The students' reading fluency of the Qur'an before learning the qiro'ati method obtained an average value of 65.27 and a standard deviation of 9.184 with the highest value being 80 and the lowest value being 52. 2) Al-Quran reading fluency. The students' Qur'an after learning the Qiro'ati method obtained an average score of 76.83 and the standard deviation was 9.337 with the highest score being 90 and the lowest 60. 3) The students' Qur'an reading fluency before and after learning the Qiro'ati method was found. difference, this is obtained from the results of the Paired Sample T-test which shows the Sig value. (2-tailed) = 0.000 which is < 0.05 or H0 is rejected.